FA02.05: PROGRESSION RATE OF BARRETT'S ESOPHAGUS FROM NATIONAL REGISTRY OF EXPERT CENTERS IS MUCH GREATER THAN ANTICIPATED FROM POPULATION STUDIES. (14th September 2018) - O'Byrne, Lisa; Verhage, Roy; O'Brien, Marie; O'Toole, Dermot; Muldoon, Cian; Buckley, Martin; Murphy, Tom; Reynolds, Rob; Patchett, Stephen; Kay, Elaine; Azam, Haleema; Ravi, Narayanasamy; et al.
Abstract: Background: Barrett's Esophagus (BE) is well established as the main pathological precursor for esophageal adenocarcinoma (EAC). Progression to high grade dysplasia (HGD) or EAC varies widely between population based studies and specialized BE registries from high volume centers. No such data existed from the Republic of Ireland until 2011 when a multicenter registry was established involving three centers to more accurately determine the risk of progression to EAC in the Irish population. Methods: A detailed clinical, endoscopic and pathological database includes 3397 patients from January 2008 to July 2017, with BE defined by the presence of specialized intestinal metaplasia (SIM). A prospective web based database was used to gather information from three designated esophageal centers with initial and follow up data abstracted by a data manager and overseen by a project manager. Results: 325 were excluded following a diagnosis of HGD or EAC at index biopsy, or being a tertiary referral, leaving 3072 with a median age of 61 and a 2.1:1 male to female ratio and a median follow up of 3 years, and 5024 person years. 127 (4%) cases progressed to HGD/EAC, 65 after one year of follow up. 55 (2%) developed EAC were identified, 30 of those within one year. The overall incidence HGD/EAC was 2.53% per year, 1.3% if the first year is excluded. The risk of progression to EAC alone was 1.09% per year, 0.5% excluding the first year. Low grade dysplasia (LGD) on index biopsy was associated with a progression rate of 11.7% per year, 4.2% with the first year excluded. Conclusion: With strict data entry and pathologic quality assurance, progression rates for non-dysplastic BE was several fold higher than population studies, highlighting caution in abstracting from population data. True LGD, as evidenced in a recent report by Kestens et al. 1 represent high risk disease, with most of the risk evident within the first year. Reference: 1. Kestens C, Offerhaus G, van Baal J, Siersema PD. Patients wtih Barrett's esophagus and persistent low-grade dysplasia have an increased risk for high- grade dysplasia and cancer. Clin Gastroenterol Hepatol. 2016;14:956–962 Disclosure: All authors have declared no conflicts of interest.